Perbedaan Pemerolehan Bahasa pada Saudara Kembar Usia 5 Tahun dengan ADD dan ASD dalam Lingkungan Linguistik yang Sama - Putu Wahyu Widiatmika; Nissa Puspitaning Adni (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study examines language acquisition in five-year-old twins with different neurodevelopmental conditions, namely Attention Deficit Disorder (ADD) and Autism Spectrum Disorder (ASD). The study aims to describe and compare the language acquisition of the two research subjects in terms of phonology, morphology, syntax, and semantics. This study employs a qualitative approach using the case study method. The research subjects are two twin boys, one of whom has ADD and the other has ASD. Data were collected through participant observation and interviews using transcription and note-taking techniques. Data analysis was conducted using a qualitative approach and presented descriptively. The results indicate that the child with ADD exhibits more developed linguistic competence compared to the child with ASD. The child with ADD is capable of acquiring language at the phonological, syntactic, and semantic levels, although inconsistencies in sound production and sentence structure are still observed. Conversely, the child with ASD has not yet demonstrated language acquisition at the word and meaning levels and remains at the babbling stage. The significant differences in language acquisition between the two study groups, despite growing up in relatively similar linguistic environments and receiving comparable linguistic stimuli, indicate that language acquisition is strongly influenced by children’s cognitive readiness and neurological conditions. This study contributes empirically by demonstrating that certain neurodivergent conditions affect children’s language acquisition progress even when they receive identical linguistic treatment.